Validação da ferramenta net promoter score (nps) para avaliação da satisfação dos pais em unidades de terapia intensiva pediátrica - Bitencourt, Victoria Noremberg (2021)
Introduction: Due to the growing demand in relation to the quality of health services, the evaluation of user / client satisfaction and, in the case of pediatrics, parental satisfaction, are increasingly being taken into account. One of the most used instruments to assess customer satisfaction is the Net Promoter Score (NPS). Widely used in the industry and services sector, the NPS has been gaining more and more space in the areas destined to health, in the world. Currently, the only validated instrument to assess satisfaction in pediatric intensive care units (PICUs) in Brazil is the Empowerment of Parents in the Intensive Care (EMPATHIC-30). Objective: To evaluate the validity of the NPS tool for assessing parental satisfaction in the PICU. Methods: Observational multicenter cross-sectional study carried out in the PICU of five hospitals in Brazil. The legal guardians for the hospitalized child, aged over 18 years, were eligible. The EMPATHIC-30 and NPS tools were applied together with a sociodemographic questionnaire. For analysis, the results of EMPATHIC-30 were dichotomized at values equal or greater than the median of the test (individuals considered satisfied with the care received in the PICU) and lower than the median (dissatisfied individuals). Results: Those responsible for 78 patients admitted to the PICUs were interviewed. Of the respondents, 85% were female and 62% were in private hospitals. The mean NPS was 9.6 ± 0.9 points, with a median of 10 [IIQ 10-10]. The EMPATHIC-30 obtained an average of 5.5 ± 0.9, with a median of 5.7 points [IIQ 5.4-5.9]. Compared to the gold standard, the NPS showed 100% sensitivity at all cutoff points, except at point 10, where the sensitivity was slightly lower (97.5%). As for specificity, performance was weaker, with values ranging from 0% (NPS ≥ 5) to 47.4% (NPS = 10). The accuracy of the NPS was 72.7%. Conclusion: The NPS was shown to be highly sensitive to assess parental satisfaction, but with weak specificity to identify dissatisfied users.